Online collaborative learning to promote teachers’ evaluative thinking - Sara Romiti; Francesco Fabbro; Maria Ranieri (Italian Journal of Educational Technology)
The study focuses on how to strengthen teachers' evaluation skills in a social and collaborative dimension. The introduction of collaborative learning modes was tested within an institutional teacher training programme via LMS. Indeed, Computer Supported Collaborative Learning (CSCL) is considered appropriate for developing reflective skills through peer exchange. The article examines the Valu.Elearn programme, aimed at in-service teachers to strengthen their evaluative competence. The study focuses on two collaborative e-activities. A total of 166 teachers and two tutors participated in these activities during the school year 2021-22. The Community of Inquiry was used as a framework for analysing the content of the forums, while the interactions between participants were examined using sociocultural discourse analysis. The findings highlight the potential and limitations of the online environment for promoting collaborative reflection on evaluation issues.